Facilitators and barriers to home blood pressure monitoring among pregnant women in Ghana: a mixed‑methods analysis of patient perspectives - Newman, N.; Beyuo, T.K; Nartey, B.A.; Segbedzi‑Rich, E.; Pangori, A.; Moyer, C.A; Lori, J.R.; Oppong, S.A; Lawrence, E.R. (BMC Pregnancy and Childbirth, 2024)
Background The benefit of home blood pressure monitoring during pregnancy and in low-resource settings is incompletely understood. The objective of this study was to explore the experiences, barriers, and facilitators of home blood pressure monitoring among pregnant women in Ghana. Methods This concurrent triangulation mixed-methods study was conducted at an urban tertiary hospital in Ghana. Participants were recruited from adult pregnant women presenting for routine antenatal care. Upon enrollment, participants’ demographics and history were collected. At the next study visit, participants received audiovisual and hands-on training on using an automatic blood pressure monitor; they then monitored and logged their blood pressure daily at home for 2–4 weeks. At the final study visit, verbally administered surveys and semi-structured interviews assessed participant’s experiences. Quantitative data were analyzed using R version 4.2.2, and frequencies and descriptive statistics were calculated. Qualitative data were imported into DeDoose 9.0.78 for thematic analysis. Results Of 235 enrolled participants, 194 completed surveys; of those, 33 completed in-depth interviews. Participants’ mean age was 31.6 (SD 5.3) years, 32.1% had not previously given birth, and 31.1% had less than a senior high school education. On a 4-point Likert scale, the majority reported they “definitely” were able to remember (n = 134, 69.1%), could find the time (n = 124, 63.9%), had the energy (n = 157, 80.9%), could use the blood pressure monitor without problems (n = 155, 79.9%), and had family approval (n = 182, 96.3%) while engaging in home blood pressure monitoring. 95.88% (n = 186) believed that pregnant women in Ghana should monitor their blood pressure at home. Qualitative thematic analysis demonstrated that most participants liked home blood pressure monitoring because of increased knowledge of their health during pregnancy. While most participants found measuring their blood pressure at home doable, many faced challenges. Participants’ experiences with five key factors influenced how easy or difficult their experience was: 1) Time, stress, and daily responsibilities; 2) Perceived importance of BP in pregnancy; 3) Role of family; 4) Capability of performing monitoring; 5) Convenience of monitoring. Conclusions Among pregnant women in urban Ghana, home blood pressure monitoring was perceived as positive, important, and doable; however, challenges must be addressed.
Research Article
Keywords: Home blood pressure monitoring; HBPM; Preeclampsia; Eclampsia; Hypertensive disorder; Pregnancy; Ghana; LMIC